Identification and functional characteristic of SARS-CoV-2-specific T lymphocytes in COVID-19 patients up to 16 months after disease onset - I. S. Vladimirov; A. S. Zhdanova; V. E. Mukhin; V. V. Makarov; V. S. Yudin; S. A. Kraevoy (Медицинская иммунология, 2024)
In cases of respiratory viral infection, along with innate immunity mechanisms, the adaptive immune system plays a crucial role in the body’s defence. The efficiency of its cellular component is crucial for pathogen elimination. T cell response is detected in almost all cases of COVID-19, being among the key factors of the virus control and resistance to infection, including re-infection. So far, however, many aspects of cellular immune response to SARS-CoV-2 over one year or later after infection remain unclear. The aim of this study was to investigate the dynamics of laboratory parameters of post-infection cellular immunity to SARS-CoV-2 within 16 months from the symptoms’ onset.Fifteen healthy volunteers and 87 COVID-19 patients were included into the study. The patients were divided into 3 groups depending on the time elapsed from the onset of the first symptoms to the time when blood samples were collected (from 14 to 500 days). For all samples, the number of S- and N-specific T lymphocytes and the cytokines secreting profiles were determined. Also, the Phenograph automatic clustering algorithm was used to discern different functional groups of the cells.Approximately 1 in 5 × 103 peripheral blood mononuclear cells was specific for SARS-CoV-2 S-protein, and 1 in 104 was specific for N-protein. Since the first weeks of infection, the number of specific CD8+ cells was significantly higher in COVID-19 patients, as compared with the group of healthy volunteers. As the postinfection period increased, the number of virus-specific CD4+ and CD8+ cells gradually decreased, but remained significantly higher than in control group. Among CD4+ cell population, the proportion of IFNγ-IL- 2-TNFα+ cells decreased and the ratio of IFNγ+IL-2-TNFα- cells increases. During first weeks of the disease, CD8+ lymphocytes are represented predominantly by IFNγ+IL-2-TNFα- cells and IFNγ-IL-2-TNFα+ cells by the end of the observation period. The clustering results showed that, in the early post-infection period, virusspecific T lymphocytes were mostly presented by populations of IFNγ- and TNFα-producing CD4+ effector memory cells. Meanwhile, in later time period, the most common populations were TNFα-producing CD8+ TEMRA and IFNγ-producing CD8+ central memory T lymphocytes.T cell adaptive immunity plays an important role in the control and elimination of viral infections. In this study, we demonstrated that robust cellular immunity against SARS-CoV-2 is present in the vast majority of patients from the first weeks up to 16 months after the onset of the first symptoms of COVID-19. The immune memory to SARS-CoV-2 is provided by production of central and effector memory T cells, and the data on their time dynamics during the study period allow us to hope for a longer duration of cellular immune memory to SARS-CoV-2.